Group Guidance on Symbolic Modeling Techniques to Enhance Online Learning Motivation for Students - Ma'ab, Husnu Ma’ab (Lembaga Bale Literasi, 2024)
The primary issue with this study is that students are not motivated to learn, as evidenced by their poor attendance records, low engagement in class, scores that fall short of the KKM, and disregard for remediation. The goal of the study is to use symbolic modeling strategies in a group guidance context to raise students' motivation for learning.The Guidance and Counseling Action Research (PTBK) research method was employed in this study, which involved seven students who had low category motivation issues during their online learning experiences. The research subjects who received group guidance were seven students from class VIII of SMPN 15 Palu. The findings revealed a difference as well as an increase in group leader and student activity, group leader activity, and the pretest-posttest averages differed. Activity increased to the good category by 25.5, moving it out of the moderate category. There was a 6.42 difference in the average score between the pretest and posttest, and the group leader's or teacher's activity in providing services saw a score increase of 27.3 from the good enough to good category. The state of this activity increase indicates that students' motivation for online learning is effectively increased through the use of the symbolic modeling technique.